ARCA SIWA MAHAGURU DI PURA SIBI AGUNG DESA PEKRAMAAN KESIAN GIANYAR KAJIAN IKONOGRAFI - Suryadi, I Made (Humanis; Volume 10. No 2. Februari 2015)
The archaeological study tries to reveal the culture history of the past thought abject that are left behind. The relict of the past basically contain very high historical values, in addiction to the informative values, the artistic values, and religious values. The culture elements of the past being studied in this research includes as small a past of an art work, namely an art sculpture. A research at The Temple of Sibi Agung in Kesian Village Gianyar was conducted by researches from The Centre for Archaeologycal heritage and preservation of Bali on 1992. However, the research was merely an inventory culture heritage in Pura Sibi Agung Kesian Village Gianyar because that are still some aspect that are still not clear. The problem that have been formulated are to know the form, function, meaning, antiquity of Siwa Mahaguru in Sibi Agung Temple Kesian Village Gianyar. The theory being applied in this research in the theory of functions, theory of semiotics, and theory of ritus. The methos that is used to address the issues that have been formulated in this research includes : the first data collection throught observation, interview and book review. The next stage is processing data using analysis of qualitative, analysis of morfology, analysis of econographic , analysis of symbol, analysis of contextual. Results of the analysis of the shape of the statue of Siwa Mahaguru at The Sibi Agung Temple Kesian Village Gianyar shows the variation of the shape of the statue based on the analysis of function, statue of Siwa Mahaguru in the Sibi Agung Temple at Kesian Village Gianyar than as worship of Dewa Siwa statue Siwa Mahaguru also functioned as a means of education. While the meaning of the statue of Siwa Mahaguru at the Sibi Agung Temple at Kesian Village Gianyar meaning believed by local people.
Keywords: Statue of Siwa Mahaguru, Sibi Agung Temple, Form, Function, meaning